Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan dengan Team Work sebagai Variabel Intervening pada CV. Saprotan Utama - Yudhistira, Ainul; Bayu Kurniawan; Prianka Ratri Nastiti (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the direct and indirect influence of Work Environment (X1) and Work Motivation (X2) on Empolyee Performance (Y) throught Team Work (Z) as a mediating variable at CV. Saprotan Utama. The method used is quantitative with a Stuctural Equation Modeling (SEM) approach using AMOS software. The research sample is CV. Saprotan Utama employees. The results of the study indicate that Work Environment, Work Motivation, and Team Work partially have a positive and significant effect on Employee Performance. Furthermore, Team Work is proven to be able to significantly mediate the relationship between Work Environment on Performance, and Work Motivation on Performance. This finding emphasizes the importance of building a conducive work environment and high motivation to improve team work, which will ultimately optimize organizational performance.